Set-theoretic geology - Fuchs, G; Hamkins, J; Reitz, J (Elsevier, 2014)
A ground of the universe V is a transitive proper class , such that and V is obtained by set forcing over W, so that for some W-generic filter . The model V satisfies the ground axiom GA if there are no such W properly contained in V. The model W is a bedrock of V if W is a ground of V and satisfies the ground axiom. The mantle of V is the intersection of all grounds of V. The generic mantle of V is the intersection of all grounds of all set-forcing extensions of V. The generic HOD, written gHOD, is the intersection of all HODs of all set-forcing extensions. The generic HOD is always a model of ZFC, and the generic mantle is always a model of ZF. Every model of ZFC is the mantle and generic mantle of another model of ZFC. We prove this theorem while also controlling the HOD of the final model, as well as the generic HOD. Iteratively taking the mantle penetrates down through the inner mantles to what we call the outer core, what remains when all outer layers of forcing have been stripped away. Many fundamental questions remain open.